NEUROENDOCRINE ACTIONS AND REGULATION OF HYPOTHALAMIC NEUROPEPTIDE Y DURING LACTATION - Crowley, W,R. (2007)
The expression of neuropeptide Y (NPY) and its co-messenger, agouti-related peptide (AgRP), in arcuate neurons of the hypothalamus is increased during lactation in rats. Our research has been addressing the questions of the physiological actions of these peptides during lactation and the physiological signals associated with lactation that result in increased expression of their genes. Our studies indicate that NPY and AgRP exert pleiotropic actions during lactation that help integrate neuroendocrine regulation of energy balance with controls over anterior and posterior pituitary hormone secretion. Further, reciprocal signaling to the NPY/AgRP system by leptin and ghrelin is responsible for the changes in expression of these hypothalamic peptides in lactating animals, and thus, may contribute to regulation of food intake and the various neuroendocrine adaptations of lactation.